Universal and switchable omni-repellency of liquid-infused surfaces for on-demand separation of multiphase liquid mixtures - Mai, Van Cuong (2022)
Mixtures of immiscible liquids are commonly found in the scenarios of environmental protection and many industrial applications. Compared to widely explored water-oil mixtures, small differences in the surface energy of organic liquids, especially for those in multiphase mixtures, make their separation a formidable challenge. Here, a family of versatile coatings based on the reactions between plant polyphenols and 3-aminopropyl triethoxysilane is introduced to regulate the wetting behavior of substrates by forming stable liquid-infused interfaces. The key finding is that when a coated substrate is prewetted with a liquid forming a stable liquid-infused interface, it becomes repellent to any other immiscible liquids. This phenomenon is independent of the surface energy of the initial wetting liquid. This exclusive wetting behavior can lead to distinctive repellency toward almost any liquid by the infusion of an immiscible liquid, even if the difference of surface energy and dielectric constant of a liquid pair is as small as 2.0 mJ m-2 and 1.8, respectively, resulting in universal and switchable omni-repellency. Of particular importance is that the as-prepared coating makes possible the on-demand separation of multiphase liquid mixtures by both continuous membrane filtration and static absorption, presenting a green and cost-effective approach to addressing this major environmental and industrial challenge.